Lack of age-dependent development of the contingent negative variation (CNV) in migraine children? - Bender, Stephan; Weisbrod, Matthias; Just, Ulrike; Pfüller, Ute; Parzer, Peter; Resch, Franz; Oelkers-Ax, Rieke (Cephalalgia, 2002)
Increased negativity of contingent negative variation (CNV) in adult migraineurs is thought to reflect cortical hyperexcitability. CNV amplitude changes with age in healthy adults. Recently, evidence emerged that this might not be the case for migraineurs. Our study investigates age-dependency of CNV during childhood age. Seventy-six healthy controls and 61 children with migraine without aura (IHS code 1.1) between 6 and 18 years were examined using an acoustic S1-S2-CNV-paradigm with a 3-s inter-stimulus interval. The amplitude of the late component of CNV, as well as total CNV at the vertex (Cz according to the international 10-20 system), were significantly higher in migraineurs without aura than in controls. Healthy controls showed increasing amplitudes of CNV with age, whereas in migraine children without aura amplitudes did not change. Thus group differences were reduced during adolescence. Increased CNV negativity might reflect a biological vulnerability to migraine, rather than being a result of chronification. Migraineurs seem to lack age-dependent development of CNV also during early age, which supports the hypothesis of migraine as a maturation disorder.